2009
DOI: 10.2341/08-073-lr
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Microleakage and the Layering Methods of Silorane-based Resin Composite in Wide Class II MOD Cavities

Abstract: Method and Materials: Thirty-two freshly extracted caries-free human third molars were used. A wide mesio-occlusal-distal (MOD) cavity was prepared in each third molar, with the occlusal dimension being approximately twothirds of the intercuspal dimension, and the cervical limit of one proximal box was stopped 1 mm below and the other 1 mm above the cementoenamel junction. The cavities were filled with a methacrylate-based nanohybrid composite (Grandio, VoCo) and a silorane-based microhybrid composite (Filtek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 29 publications
(28 reference statements)
7
89
1
1
Order By: Relevance
“…14 Although several recent studies have evaluated physicochemical properties of silorane-based resins, [13][14][15][16][17] research on their biologic effects is quite limited, being based mostly on in vitro and cell culture studies. 5,10,18 To the best of our knowledge, the in vivo pulpal and periapical response to these new restorative systems has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although several recent studies have evaluated physicochemical properties of silorane-based resins, [13][14][15][16][17] research on their biologic effects is quite limited, being based mostly on in vitro and cell culture studies. 5,10,18 To the best of our knowledge, the in vivo pulpal and periapical response to these new restorative systems has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that various traditionally used composite materials, due to a difference in their chemical compositions, may have a different marginal integrity, and therefore caution is advised when interpreting the comparable results. In a previous study on microleakage of Class II fillings by method of sample-cutting, Bagis et al 17) did not find that silorane fillings had any marginal leakages. The differences between the present study and Bagis' study could be attributed to different shapes of the cavities examined.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have described their promising low shrinkage. 10,11 Bagis and others 19 restored class II cavities with both silorane-based and conventional resin composite and observed that only the silorane group showed no leakage at enamel and dentin margins. With respect to these potential benefits, additional studies examining polymerization performance and microhardness with various LCUs are warranted.…”
Section: Discussionmentioning
confidence: 99%